Short-term dietary choline supplementation alters the gut microbiota and liver metabolism of finishing pigs - Xie, Zhongwei; Du, Junhua; Gan, Mailin; Zhou, Chengpeng; Li, Menglin; Liu, Chengming; Wang, Meng; Chen, Lei; Zhao, Ye; Wang, Yan; Jiang, Yanzhi; Cheng, Wenqiang; et al. (Frontiers in Microbiology, 2023)
Choline is an essential nutrient for pig development, and play a role in growth performance, carcass characteristics as well as reproduction in weaned pigs and sows, respectively. However, the effect of choline on finishing pigs and its potential regulatory mechanism remains unclear. Here we feed finishing pigs with 1% the hydrochloride salt of choline such as choline chloride (CHC) under a basic diet condition for a short term (14 days). A 14-day supplementation of CHC significantly increased final weight and carcass weight, while has no effect on carcass length, average backfat and eye muscle area compared with control pigs. Mechanically, CHC resulted in a significant alteration of gut microbiota composition in finishing pigs, and remarkably increased relative abundance of bacteria contributing to growth performance and health including Prevotella, Ruminococcaceae and Eubacterium. In addition, untargeted metabolomics analysis identified 84 differently abundant metabolites in liver between CHC pigs and control pigs, of which most metabolites were mainly enriched in signaling pathways related to improvement of growth, development and health. Notably no significant difference in ability of oxidative stress resistance between two groups, although increased bacteria and metabolites keeping balance in reactive oxygen species showed in finishing pigs after CHC supplementation. Taken together, our results suggest that a short-term supplementation of CHC contribute to increase body weight gain and carcass weight of finishing pigs, which may be involved in regulation of gut microbiota and alterations of liver metabolism, providing new insights This is a provisional file, not the final typeset article into potential of choline-mediated gut microbiota/metabolites in improving growth performance, carcass characteristics as well as health.